Association between intake of red and processed meat and survival in patients with colorectal cancer in a pooled analysis - Carr, Prudence R.; Chang-Claude, Jenny; Brenner, Hermann; Hoffmeister, Michael (Clinical gastroenterology and hepatology, 2019)
BACKGROUND & AIMS: Red and processed meat intake is associated with colorectal cancer (CRC) incidence, but it is not clear if intake is associated with patient survival after diagnosis. - METHODS: We pooled data from 7627 patients with stage I-IV CRC from 10 studies in the International Survival Analysis in Colorectal Cancer Consortium. Cox proportional hazards regression models were used to evaluate the associations of intake of red and processed meat before diagnosis with overall and CRC-specific survival. - RESULTS: Among 7627 patients with CRC, 2338 died, including 1576 from CRC, over a median follow-up time of 5.1 years. In multivariable-adjusted analyses, higher intake of red or processed meat was not associated with overall survival of patients with stage I-III CRC: Q4 vs Q1 red meat hazard ratio [HR], 1.08 (95% CI, 0.93-1.26) and Q4 vs Q1 processed meat HR, 1.10 (95% CI, 0.93-1.32) or with CRC-specific survival: Q4 vs Q1 red meat HR, 1.09 (95% CI, 0.89-1.33) and Q4 vs Q1 processed meat HR, 1.11 (95% CI, 0.87-1.42). Results were similar for patients with stage IV CRC. However, patients with stage I-III CRC who reported an intake of processed meat above the study-specific medians had a higher risk of death from any cause (HR, 1.12; 95% CI, 1.01-1.25) than patients who reported eating at or less than the median. - CONCLUSION: In this large consortium of CRC patient cohorts, intake of red and processed meat before a diagnosis of CRC was not associated with shorter survival time after diagnosis, although a possible weak adverse association cannot be excluded. Studies that evaluate dietary data from several time points before and after cancer diagnosis are required to confirm these findings.
Gesehen am 14.08.2019